Health Education for Bed Bug Control Among Islamic Boarding School Students in Semarang City - Martini, Martini; Adi, Mateus Sakundarno; Kusariana, Nissa; Udiyono, Ari; Fauzi, Muh (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2026)
Bed bugs (Cimex spp.), locally known as tinggi, kepinding, or tumbila, are blood-sucking insects that inhabit dark, damp areas, including mattresses and sofas. The two main species are Cimex lectularius and Cimex hemipterus, with C. hemipterus being common in tropical regions, including Indonesia. Although their prevalence previously declined, bed bug infestations have re-emerged in recent decades, largely due to increased mobility of people and goods. This activity was conducted at the At-Taqwa Orphanage in Semarang City to improve students’ knowledge of bed bugs and their control through health education. This community service activity used a one-group pre-test and post-test design and involved 22 participants. The activities included a pre-test, an interactive education session, and a post-test. The results showed that most participants were unaware of bed bugs or their presence before the intervention. After the educational session, participants demonstrated a significant increase in knowledge and awareness. In addition to improving knowledge, this activity produced a positive outcome by strengthening participants’ awareness and their ability to independently implement bed bug prevention measures in their living environment. Health education was effective as a preventive strategy, and similar programs should be implemented regularly to improve environmental hygiene and overall public health quality.